Mechanical characterization of 3/2 fibre metal laminate materials - M. F., Rani; M. R. M., Rejab; M. I., Ibrahim; N. K., Romli (Faculty Mechanical Engineering, UMP, 2023)
Development of lightweight materials onto vehicle bodies, especially in the automotive sector is seen as one of the best alternative solutions in order to reduce fuel consumption and decrease harmful emissions produced by the emission. Reducing in weight of a vehicle can improve fuel efficiency with no prejudice to safety strength requirements. Fibre metal laminate (FML) is hybrid composite structure based on thin sheet of metal alloys and plies of fibre reinforced polymeric materials which offer the ability of superior mechanical properties such as lightweight, high fatigue growth resistance and high strength and stiffness. Multi-material auto bodies will allow optimal material selection in structural components for higher performance and lower cost. This study aims to fabricate and investigate the failure behaviour of a 3/2 layer fibre metal laminate subjected to the quasi-static indentation test. The FML is constructed from aluminium 2024-T3 and layered with composite materials CFRP, GFRP and SRPP. The crosshead speed test analysis ran in different parameters on 1 mm/min, 5 mm/min, 10 mm/min and 50 mm/min, respectively in quasi-static indentation test. The experimental performances of each specimen were compared to predict the behaviour and performance of the FML composite. The test indicates that varying crosshead speeds have influenced the affected region of the FML, causing debonding on the laminate as a result of continued loading.